Equine Arteritis Virus Elicits a Mucosal Antibody Response in the Reproductive Tract of Persistently Infected Stallions - Carossino, Mariano (Clin Vaccine Immunol, 2017)
Equine arteritis virus (EAV) has the ability to establish persistent infection in the reproductive tract of the stallion (carrier) and is continuously shed in its semen. We have recently demonstrated that EAV persists within stromal cells and a subset of lymphocytes in the stallion accessory sex glands in the presence of a significant local inflammatory response. In the present study, we demonstrated that EAV elicits a mucosal antibody response in the reproductive tract during persistent infection with homing of plasma cells into accessory sex glands. The EAV-specific immunoglobulin isotypes in seminal plasma included IgA, IgG1, IgG3/5, and IgG4/7. Interestingly, seminal plasma IgG1 and IgG4/7 possessed virus-neutralizing activity, while seminal plasma IgA and IgG3/5 did not. However, virus-neutralizing IgG1 and IgG4/7 in seminal plasma were not effective in preventing viral infectivity. In addition, the serological response was primarily mediated by virus-specific IgM and IgG1, while virus-specific serum IgA, IgG3/5, IgG4/7, and IgG6 isotype responses were not detected. This is the first report characterizing the immunoglobulin isotypes in equine serum and seminal plasma in response to EAV infection. The findings presented herein suggest that while a broader immunoglobulin isotype diversity is elicited in seminal plasma, EAV has the ability to persist in the reproductive tract, in spite of local mucosal antibody and inflammatory responses. This study provides further evidence that EAV employs complex immune evasion mechanisms during persistence in the reproductive tract that warrant further investigation.